A Study of Achievement in Health on Life Safety of Matthayomsuksa 2 Students by Cooperative Leaning Using STAD Technique - Phongpaew, Napassorn (Journal of Dhamma for Life, 2025)
This study aimed to investigate and compare the learning achievement in Health Education on the topic of “Life Safety” among Mathayom Suksa 2 (Grade 8) students before and after applying the Student Teams Achievement Division (STAD) cooperative learning technique. The sample consisted of 35 Mathayom Suksa 2 students from a secondary school, selected through cluster sampling. The research instruments included 13 lesson plans based on the STAD technique and a 35-item multiple-choice achievement test with four options. The reliability coefficient of the test, measured using the KR-20 method, was 0.91. Data were analyzed using descriptive statistics including percentage, mean, and standard deviation, as well as inferential statistics using a dependent samples t-test. The research findings revealed that: (1) 77.14% of the students attained a good level of achievement or higher after learning through the STAD technique; and (2) the post-test scores were significantly higher than the pre-test scores at the .05 level of significance. These results indicate that the STAD cooperative learning technique effectively enhanced students’ learning achievement in Health Education on the topic of life safety.